Unleashing the Power of TypeScript - Kinney, Steve (SitePoint, 2023)
If you're a JavaScript developer struggling to get to grips with TypeScript or use it effectively in your projects, this book will guide you in making the most of this powerful language and its latest features, and help you overcome some common misunderstandings and pitfalls. TypeScript 5.0 is a major advancement to the user-friendliness and flexibility of the language. It nudges us toward better coding practices, promotes cleaner code, and catches potential errors before they become a headache. It's a great time to start using TypeScript, but if you're a JavaScript developer struggling to get to grips with the language or use it effectively in your projects, this short book is for you. It will guide you in making the most of this powerful language and its latest features, and help you overcome some common misunderstandings and pitfalls. It covers: * Simplifying Reducers in React with TypeScript * A Gentle Introduction to Generics in TypeScript * Navigating the Perils and Pitfalls of Using React's Context API with TypeScript * Extending DOM Elements and Creating Polymorphic Components * A Guided Tour of the Three Biggest Features in TypeScript 5.0 This book is for intermediate-level JavaScript developers who want to get to grips with the powerful features that TypeScript offers.